Probiotic properties of Lactobacillus spp. from Lake Victoria as potential feed supplement in aquaponic production system - TyNiah Dates; Loretta Harrison; Cersey Ochieng Onyango; Lucy Aketch Wanga; Oscar Omondi Donde; Anne Osano; Joshua Ogendo (The Microbe)
The increasing reliance on antimicrobials in aquaculture to manage fish diseases has contributed to the spread of antimicrobial-resistant pathogens, necessitating alternative solutions. Probiotics are live microorganisms that confer health benefits, have emerged as a promising strategy to enhance fish health, digestion, and environmental sustainability. However, many probiotic applications in aquaculture utilize terrestrial-derived strains, despite the advantages of host-specific probiotics adapted to aquatic environments. This study aimed to isolate and evaluate the probiotic potential of Lactobacillus species from the water, sediments, skin, gills, and intestines of Nile tilapia (Oreochromis niloticus) from the Nyanza Gulf of Lake Victoria. Samples were collected from both cage-cultured and free-range fish, and bacterial isolation was conducted using De Man- Rogosa- Sharpe (MRS) agar, followed by morphological and biochemical characterization. The isolates were assessed for probiotic attributes, including acid and salt tolerance, and antimicrobial activity against Escherichia coli and Staphylococcus aureus using the disc diffusion method. Ten Lactobacillus isolates were identified, all exhibiting gram-positive characteristics and catalase negativity. Most isolates showed high acid tolerance, maintaining over 70 % viability at pH 3.0, and demonstrated resilience to high salt concentrations (4.5 % and 6.5 %). Antimicrobial assays revealed that isolate 1 exhibited the strongest inhibitory effects. These findings suggest that Lactobacillus isolates from Nile tilapia possess promising probiotic properties and could serve as effective feed supplements in aquaponics and sustainable aquaculture. Further in vivo studies are recommended to evaluate their efficacy in improving fish health and growth.